Sleeve material for molding aspheric glass lens and preparation method thereof

By adding Si3N4 powder to WC powder, a WC-based carbide sleeve material with low thermal expansion coefficient was prepared, which solved the problem of high thermal expansion coefficient of existing WC-based optical mold materials, and achieved both high hardness and low thermal expansion coefficient, which was suitable for the molding process of aspherical glass lenses.

CN119638427APending Publication Date: 2025-03-18ANHUI SHANGXINJINGGONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411787766.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing WC-based optical mold materials have a high thermal expansion coefficient, which cannot meet the needs of lower thermal expansion coefficient, affecting the precision of mold design and processing capabilities.

Method used

By adding Si3N4 powder to the WC powder, a WC-based carbide sleeve material with a low thermal expansion coefficient was prepared, and a process step such as ball milling, drying, prepressing, and sintering was used to form a material with high hardness and low thermal expansion coefficient.

Benefits of technology

The goal of reducing the thermal expansion coefficient while maintaining high hardness and wear resistance is achieved, and is suitable for the molding process of aspherical glass lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638427A_ABST
    Figure CN119638427A_ABST
Patent Text Reader

Abstract

The invention provides a sleeve material for molding an aspheric glass lens and a preparation method of the sleeve material. The method comprises the steps that 1, raw material powder is mixed and dried, tungsten carbide powder and Si3N4 powder are mixed in a ball milling tank in an inert atmosphere to obtain composite powder, and the adding amount of the Si3N4 powder is 1 wt%-15 wt%; (2) die filling; putting the composite powder into a graphite female die, and pre-pressing under the pressure of 5-20 MPa; (3) sintering is conducted, specifically, the mold is placed in an SPS system, the initial axial pressure ranges from 5 MPa to 10 MPa, vacuumizing is conducted till the pressure is 10 Pa or below, gradient heating sintering is conducted, the highest sintering temperature ranges from 1500 DEG C to 1900 DEG C, the highest sintering pressure ranges from 40 MPa to 60 MPa, and after heat preservation is finished, the mold is taken out after cooling; and (4) sampling: carrying out sand blasting treatment on the graphite on the surface of the sample to obtain the sleeve material for molding the aspheric glass lens. The material has a lower thermal expansion coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder metallurgy, and in particular, relates to a sleeve material for molding an aspherical glass lens and a preparation method thereof. The sleeve material for molding an aspherical glass lens is a WC-based cemented carbide with a low thermal expansion coefficient. Background Art

[0002] Optical glass precision molding technology uses high-precision molds and special molding equipment to mold optical glass from the transition point to the softening point into the required optical element in one go. It has the advantages of low cost, high efficiency, near net shape and environmental friendliness, and is widely used in aspheric optical elements, optical diffraction elements, optical array elements, gratings, etc. WC-based cemented carbide has excellent properties such as high hardness, high strength, high wear resistance, good corrosion resistance, high surface finish and good electrical processing. As a mold material, it is widely used in the molding process of aspheric glass lenses.

[0003] At present, the commonly used WC-based optical mold materials can achieve a minimum thermal expansion coefficient of 4.8 to 5.0×10 -6 / K (1073K), which is quite different from the thermal expansion coefficient of glass materials, and requires high precision in mold design and high processing capabilities of superhard materials. Therefore, the demand for WC-based cemented carbide optical mold materials with lower thermal expansion coefficients is becoming more and more urgent. Summary of the invention

[0004] Technical issues

[0005] In view of the above problems, the present invention proposes a sleeve material for molding aspheric glass lenses and a preparation method thereof. The sleeve material for molding aspheric glass lenses is a WC-based cemented carbide with a low thermal expansion coefficient. While meeting the requirements of optical mold materials for hardness and smoothness, it has a lower thermal expansion coefficient.

[0006] Technical Solution

[0007] The invention provides a method for preparing a sleeve material for molding an aspheric glass lens, and the sleeve material for molding an aspheric glass lens prepared by the method.

[0008] According to a first aspect of the present invention, there is provided a method for preparing a sleeve material for molding an aspherical glass lens, comprising the following steps:

[0009] Step 1), mixing and drying raw material powders: tungsten carbide powder and silicon nitride powder (Si3N4 powder) are mixed in a ball mill in an inert atmosphere to obtain a composite powder. The mixed powder is dried and sieved, and then stored in an inert atmosphere. The amount of Si3N4 powder added is 1wt% to 15wt% relative to the total mass of the composite powder;

[0010] Step 2), mold assembly: put the composite powder into a graphite female mold and pre-press it at a pressure of 5-20MPa; after pre-pressing, adjust the height of the upper and lower pressure heads so that the height exposed from the female mold is consistent, and the outer circle and upper and lower surfaces of the mold are wrapped with graphite felt with a thickness greater than 5mm;

[0011] Step 3), sintering: placing the assembled graphite mold in a spark plasma sintering system, with an initial axial pressure of 5 to 10 MPa, evacuating to below 10 Pa, and starting power-on sintering; adjusting the heating rate by current to achieve gradient temperature rise sintering, with a maximum sintering temperature of 1500°C to 1900°C, a holding time of 0 to 3 min, and a maximum sintering pressure of 40 to 60 MPa. After the holding is completed, the current is cut off, the temperature is cooled by water through a cooling system, and the mold is taken out after reaching room temperature;

[0012] Step 4), sampling: take out the sample, and use sandblasting to treat the graphite on the surface of the sample to obtain a sleeve material for molding an aspherical glass lens.

[0013] Preferably, the WC powder has an average particle size of 0.2 to 1 micrometer and a purity of 99.9 wt % or more.

[0014] Preferably, the average particle size of the Si3N4 powder is 1 to 5 microns, and the purity is greater than 95%, more preferably greater than 99%.

[0015] Preferably, the composite powder further comprises an inhibitor, which is chromium carbide and / or vanadium carbide. Relative to the total weight of the WC powder, the amount of the inhibitor is 0wt% to 1.5wt%, preferably 0.5wt% to 1.5wt%.

[0016] Preferably, the composite powder does not contain a binder, that is, does not contain any of cobalt, nickel and iron.

[0017] Preferably, planetary ball milling, drum wet milling or tiltable wet milling, as well as other commonly used mixing methods in the industry, can be used for mixing. The inner wall of the barrel is made of cemented carbide. The ball-to-material ratio is 3 to 5:1, the grinding ball is a cemented carbide ball, the ball milling speed is 30 to 200 r / min, and the ball milling time is 24 to 72 hours.

[0018] Preferably, the composite powder is dried, sieved and stored under a nitrogen atmosphere, and the purity of the nitrogen is greater than 99.99%.

[0019] Preferably, during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000° C., the heating rate is 30 to 100° C. / min. When the temperature is greater than 1000° C., the heating rate is 10 to 30° C. / min.

[0020] Preferably, during the sintering process, a gradient pressurization method is used for sintering. When the temperature reaches above 1000° C., the sintering pressure is 15 to 25 MPa. When the temperature reaches above 1400° C., the sintering pressure increases to 40 to 60 MPa.

[0021] Preferably, after the insulation is completed, the sintering pressure is reduced to 5-10 MPa.

[0022] According to a second aspect of the present invention, there is provided a sleeve material for molding an aspherical glass lens, which is prepared by the method for preparing a sleeve material for molding an aspherical glass lens according to the present invention.

[0023] Preferably, the thermal expansion coefficient of the sleeve material for molding the aspherical glass lens at 800°C is 4.1 to 4.5×10 -6 / K, more preferably 4.2 to 4.4×10 -6 / K.

[0024] Preferably, the hardness of the sleeve material for molding the aspherical glass lens is 1600-2100 HV30.

[0025] Preferably, the fracture toughness of the sleeve material for molding the aspherical glass lens is 6.2 to 7.2 MPa·m 1 / 2 .

[0026] Beneficial Effects

[0027] In the present invention, a sleeve material for molding an aspherical glass lens is prepared by adding Si3N4 powder to WC powder. The sleeve material has high hardness, high wear resistance, good surface finish, and a relatively lower thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The following is a graph showing the thermal expansion of the sleeve material for molding an aspherical glass lens prepared according to Example 1 at different temperatures. DETAILED DESCRIPTION

[0029] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0030] First, cut the graphite paper according to the size of the graphite negative mold and place it on the inner wall of the negative mold, and make it fit the inner wall perfectly; then put the lower pressure head into the graphite negative mold, and put in two layers of graphite paper with the same diameter as the pressure head to make it fit the pressure head; then put the composite powder mixed and dried in proportion into the graphite negative mold; finally, put in two layers of graphite paper and the upper pressure head in turn, and use a hydraulic press to apply pre-pressure and maintain pressure; after the above work is completed, use high-temperature graphite felt to wrap the mold. The size of the graphite mold and pressure head is determined by the size of the sample to be prepared.

[0031] The average particle size of Si3N4 powder is 1.5 microns, and the purity is greater than 99%;

[0032] The average particle size of WC powder is 0.8 micrometers and the purity is greater than 99.9%.

[0033] Unless otherwise specified, 0.9 wt % of vanadium carbide was added to the WC powder used in the examples and comparative examples before use. That is, the WC powder used in the examples and comparative examples was a WC powder containing 0.9 wt % of vanadium carbide.

[0034] The spark plasma sintering system used in the following examples is from SINTER LAND Co., Ltd. of Japan, and the models are LABOX-350, LABOX-6020 and continuous production line. It should be noted that the preparation of cemented carbide blocks using the method of the present invention and equipment of other manufacturers and models is also within the protection scope of the present invention. Spark plasma sintering includes pulse power-on pressure sintering, electric field assisted sintering, pulse current rapid sintering and the like.

[0035] The density results in the following examples were measured using the Archimedes displacement method;

[0036] The hardness test was obtained using a Vickers hardness tester under a load of 30 kg and maintained for 15 s;

[0037] The fracture toughness test complies with the international standard ISO 28079-2009 "Hardmetals-Palmqvist toughnesstest". The total length of the four cracks at the indentation tip is measured and calculated, and the fracture toughness KIC is calculated in combination with the Vickers hardness value of the sample under the indentation.

[0038] Test method for thermal expansion coefficient: According to the national standard GB / T 4339-2008 "Determination of thermal expansion characteristic parameters of metal materials", the thermal expansion coefficient of the test sample is within the specified range.

[0039] Example 1

[0040] A sleeve material for molding φ80mm×5mm aspherical glass lenses was prepared, wherein the mass ratio of WC:Si3N4 in the composite powder was 97:3.

[0041] 1. Powder mixing: 2000 g of the powder weighed according to the above mass ratio was placed in a cemented carbide wet grinding jar and ball milled under a nitrogen atmosphere, wherein the abrasive was a cemented carbide ball, the ball-to-material ratio was 3.5:1, the ball milling speed was 55 r / min, and the ball milling time was 48 h. The powder after ball milling was dried and sieved at a drying temperature of 80°C and stored under a nitrogen atmosphere.

[0042] 2. Mold loading: Place the dried composite powder into a graphite female mold and pre-press it with a hydraulic press at a pre-pressing pressure of 15 MPa.

[0043] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 10MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 40°C / min, and when the temperature is greater than 1000°C, the heating rate is 20°C / min.

[0044] Sintering is carried out by gradient pressure. When the temperature reaches above 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches above 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1720℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0045] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the sample surface to obtain the sleeve material for aspheric glass lens molding. After fine processing, there are no white spots and edge collapse defects on the surface, the hardness is greater than 1800HV30, there is no hole defect, and the fracture toughness is greater than 6.5MPa·m 1 / 2 . Figure 1 The thermal expansion of the sleeve material for molding the aspherical glass lens prepared according to Example 1 at different temperatures is shown in the figure, wherein the thermal expansion coefficient is 4.4×10 -6 / K(800℃).

[0046] Example 2

[0047] A sleeve material for molding a φ30mm×30mm aspheric glass lens was prepared, wherein the mass ratio of the composite powder component WC∶Si3N4=96∶4.

[0048] 1. Powder mixing: 300 g of the powder weighed according to the above weight ratio is placed in a carbide ball milling jar for planetary ball milling, wherein the abrasive is carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 200 r / min, and the ball milling time is 12 h. The powder after ball milling is dried and sieved at a drying temperature of 70°C and stored under a nitrogen atmosphere.

[0049] 2. Mold loading: Place the composite powder obtained after drying into a graphite female mold and pre-press it using a hydraulic press with a pre-pressing pressure of 20 MPa.

[0050] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 20MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 80°C / min, and when the temperature is greater than 1000°C, the heating rate is 30°C / min.

[0051] Sintering is carried out by gradient pressure. When the temperature reaches above 1000℃, the sintering pressure increases to 25MPa, and when the temperature reaches above 1400℃, the sintering pressure increases to 50MPa. The highest sintering temperature is 1780℃, and the sintering ends after 0min of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the temperature is cooled down by the water cooling system and taken out at room temperature.

[0052] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the sample surface to obtain the sleeve material for aspheric glass lens molding. After fine processing, there are no white spots and edge collapse defects on the surface. The hardness is greater than 1900HV30, there is no hole defect, and the fracture toughness is greater than 6.6MPa·m 1 / 2 , the thermal expansion coefficient is 4.3×10 -6 / K(800℃).

[0053] Example 3

[0054] A sleeve material for molding φ100mm×55mm aspheric glass lenses was prepared, with a composite powder mass ratio of WC:Si3N4=95:5.

[0055] 1. Powder mixing: 30 kg of the powder weighed according to the above weight ratio is put into a tilting wet mill for mixing, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 38 r / min, and the ball milling time is 48 h. The powder after ball milling is dried and sieved at a drying temperature of 70°C and stored under a nitrogen atmosphere.

[0056] 2. Mold loading: Place the composite powder obtained after drying into a graphite female mold and pre-press it using a hydraulic press with a pre-pressing pressure of 20 MPa.

[0057] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 30°C / min, and when the temperature is greater than 1000°C, the heating rate is 13°C / min.

[0058] Sintering is carried out by gradient pressure. When the temperature reaches above 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches above 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1680℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0059] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the sample surface to obtain the sleeve material for aspheric glass lens molding. After fine processing, there are no white spots and edge collapse defects on the surface, the hardness is greater than 1800HV30, there is no hole defect, and the fracture toughness is greater than 6.5MPa·m 1 / 2 , the thermal expansion coefficient is 4.3×10 -6 / K(800℃).

[0060] Example 4

[0061] The sleeve material for molding φ100mm×55mm aspheric glass lenses was prepared, with the composite powder mass ratio of WC∶Si3N4=92∶8.

[0062] 1. Powder mixing: 30 kg of the powder weighed according to the above weight ratio is put into a tilting wet mill for mixing, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 38 r / min, and the ball milling time is 48 h. The powder after ball milling is dried and sieved at a drying temperature of 70°C and stored under a nitrogen atmosphere.

[0063] 2. Mold loading: Place the composite powder obtained after drying into a graphite female mold and pre-press it using a hydraulic press with a pre-pressing pressure of 20 MPa.

[0064] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 30°C / min, and when the temperature is greater than 1000°C, the heating rate is 13°C / min.

[0065] Sintering is carried out by gradient pressure. When the temperature reaches above 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches above 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1640℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0066] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the sample surface to obtain the sleeve material for aspheric glass lens molding. After fine processing, there are no white spots and edge collapse defects on the surface, the hardness is greater than 1700HV30, there is no hole defect, and the fracture toughness is greater than 6.5MPa·m 1 / 2 , the thermal expansion coefficient is 4.25×10 -6 / K(800℃).

[0067] Example 5

[0068] The sleeve material for molding φ100mm×55mm aspheric glass lenses was prepared, with the composite powder mass ratio of WC∶Si3N4=87∶13.

[0069] 1. Powder mixing: 30 kg of the powder weighed according to the above weight ratio is put into a tilting wet mill for mixing, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 38 r / min, and the ball milling time is 48 h. The powder after ball milling is dried and sieved at a drying temperature of 70°C and stored under a nitrogen atmosphere.

[0070] 2. Mold loading: Place the composite powder obtained after drying into a graphite female mold and pre-press it using a hydraulic press with a pre-pressing pressure of 20 MPa.

[0071] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 30°C / min, and when the temperature is greater than 1000°C, the heating rate is 13°C / min.

[0072] Sintering is carried out by gradient pressure. When the temperature reaches above 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches above 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1650℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0073] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the sample surface to obtain the sleeve material for aspheric glass lens molding. After fine processing, there are no white spots and edge collapse defects on the surface, the hardness is greater than 1650HV30, there is no hole defect, and the fracture toughness is greater than 6.8MPa·m 1 / 2 , the thermal expansion coefficient is 4.21×10 -6 / K(800℃).

[0074] Comparative Example 1

[0075] A cemented carbide block material of pure WC powder with a size of φ1000 mm×40 mm was prepared. The raw material was the same as the WC powder raw material used in Example 1.

[0076] 1. Mold loading: Put the WC powder raw material powder into the graphite female mold and pre-press it with a hydraulic press with a pre-pressing pressure of 20MPa.

[0077] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 30°C / min, and when the temperature is greater than 1000°C, the heating rate is 13°C / min.

[0078] Sintering is carried out by gradient pressure. When the temperature reaches 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1700℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0079] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the surface of the sample to obtain the cemented carbide material. After fine processing, there are no defects such as cracks and edge collapse on the surface. The hardness is greater than 2400HV30, there are slight hole defects, and the fracture toughness is greater than 6.8MPa·m 1 / 2 , the thermal expansion coefficient is 5.1×10 -6 / K(800℃).

[0080] Comparative Example 2

[0081] A cemented carbide block material of φ100mm×55mm was prepared, with a composite powder mass ratio of WC∶Si3N4=95∶5.

[0082] 1. Powder mixing: 30 kg of the powder weighed according to the above weight ratio is put into a tilting wet mill for mixing, wherein the abrasive is a carbide ball, the ball-to-material ratio is 3.5:1, the ball milling speed is 38 r / min, and the ball milling time is 48 h. The powder after ball milling is dried and sieved at a drying temperature of 70°C and stored under a nitrogen atmosphere.

[0083] 2. Mold loading: Place the composite powder obtained after drying into a graphite female mold and pre-press it using a hydraulic press with a pre-pressing pressure of 20 MPa.

[0084] 3. Sintering: Place the assembled graphite mold in a spark plasma sintering system, set the initial axial pressure to 5MPa, evacuate to below 10Pa, and start sintering with power on; during the sintering process, a gradient temperature increase method is used for sintering. When the temperature is less than or equal to 1000°C, the heating rate is 30°C / min, and when the temperature is greater than 1000°C, the heating rate is 13°C / min.

[0085] Sintering is carried out by gradient pressure. When the temperature reaches 1000℃, the sintering pressure increases to 20MPa, and when the temperature reaches 1400℃, the sintering pressure increases to 40MPa. The highest sintering temperature is 1500℃, and the sintering ends after 3 minutes of heat preservation. After the heat preservation ends, the sintering pressure drops to 10MPa, and the water cooling system cools down to room temperature and takes it out.

[0086] 4. Sampling: Take out the sample with a hydraulic press, and use sandblasting to remove the graphite on the surface of the sample to obtain the cemented carbide material. After fine processing, there are no defects such as white spots and edge collapse on the surface. The hardness is 1500HV30, there is no hole defect, and the fracture toughness is 5.2MPa·m 1 / 2 , the thermal expansion coefficient is 4.7×10 -6 / K(800℃).

[0087] It can be seen from the above embodiments and comparative examples that the WC-based cemented carbide with Si3N4 powder added has high hardness and high wear resistance as well as a relatively lower thermal expansion coefficient, and is suitable for use as a sleeve material for molding aspherical glass lenses.

[0088] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a sleeve material for molding an aspherical glass lens, characterized in that: The method comprises the following steps: Step 1), mixing and drying raw powders: tungsten carbide powder and silicon nitride Si3N4 powder are mixed in a ball mill in an inert atmosphere to obtain a composite powder. The mixed powder is dried and sieved, and then stored in an inert atmosphere. The amount of Si3N4 powder added is 1wt% to 15wt% relative to the total mass of the composite powder; Step 2), mold assembly: put the composite powder into a graphite female mold and pre-press it at a pressure of 5-20MPa; after pre-pressing, adjust the height of the upper and lower pressure heads so that the height exposed from the female mold is consistent, and the outer circle and upper and lower surfaces of the mold are wrapped with graphite felt with a thickness greater than 5mm; Step 3), sintering: placing the assembled graphite mold in a spark plasma sintering system, with an initial axial pressure of 5 to 10 MPa, evacuating to below 10 Pa, and starting power-on sintering; adjusting the heating rate by current to achieve gradient temperature rise sintering, with a maximum sintering temperature of 1500°C to 1900°C, a holding time of 0 to 3 min, and a maximum sintering pressure of 40 to 60 MPa. After the holding is completed, the current is cut off, the temperature is cooled by water through a cooling system, and the mold is taken out after reaching room temperature; Step 4), sampling: take out the sample, and use sandblasting to treat the graphite on the surface of the sample to obtain a sleeve material for molding an aspherical glass lens.

2. The method for preparing a sleeve material for molding an aspherical glass lens according to claim 1, characterized in that: The WC powder has an average particle size of 0.2 to 1 micrometer and a purity of 99.9 wt% or more; and / or The average particle size of Si3N4 powder is 1 to 5 microns, and the purity is greater than 95%.

3. The method for preparing a sleeve material for molding an aspherical glass lens according to claim 1, characterized in that: The composite powder further comprises 0 wt % to 1.5 wt % of an inhibitor relative to the total weight of the WC powder. The inhibitor is chromium carbide and / or vanadium carbide.

4. The method for preparing a sleeve material for molding an aspherical glass lens according to claim 1, characterized in that: The composite powder does not contain a binder.

5. The method for preparing a sleeve material for molding an aspherical glass lens according to claim 1, characterized in that: The materials are mixed by planetary ball mill, roller wet mill or tiltable wet mill, the ball-to-material ratio is 3-5:1, the grinding balls are carbide balls, the ball mill speed is 30-200 r / min, and the ball mill time is 24-72 h; and / or The composite powder is dried, sieved and stored under a nitrogen atmosphere, and the purity of the nitrogen is greater than 99.99%.

6. The method for preparing a sleeve material for molding an aspherical glass lens according to claim 1, characterized in that: In the sintering process of step 3), a gradient temperature increase method is adopted for sintering. When the temperature is less than or equal to 1000° C., the heating rate is 30 to 100° C. / min. When the temperature is greater than 1000° C., the heating rate is 10 to 30° C. / min.

7. The method for preparing a sleeve material for molding an aspherical glass lens according to any one of claims 1 to 6, characterized in that: In step 3), the sintering is performed by gradient pressure, when the temperature reaches above 1000° C., the sintering pressure is 15-25 MPa, when the temperature reaches above 1400° C., the sintering pressure is 40-60 MPa; and / or After the insulation is completed, the sintering pressure drops to 5-10MPa.

8. A sleeve material for molding an aspherical glass lens, characterized in that: The aspherical glass lens is prepared by the method for preparing a sleeve material for molding an aspherical glass lens according to any one of claims 1 to 7.

9. The sleeve material for molding an aspherical glass lens according to claim 8, characterized in that: The thermal expansion coefficient of the sleeve material for molding the aspherical glass lens at 800°C is 4.1 to 4.5×10 -6 / K.

10. The sleeve material for molding an aspherical glass lens according to claim 8 or 9, characterized in that: The thermal expansion coefficient of the sleeve material for molding the aspherical glass lens at 800°C is 4.2 to 4.5×10 -6 / K; and / or The hardness of the sleeve material for molding the aspherical glass lens is 1600-2100 HV30; and / or The fracture toughness of the sleeve material for molding the aspherical glass lens is 6.2-7.2 MPa·m 1 / 2 .

Citation Information

Cited By

  • Large-size optical mold material for aspheric glass lens mold pressing and preparation method of large-size optical mold material

    CN120192164A

  • Large-size optical mold material for aspheric glass lens molding and preparation method thereof

    CN120192164B

  • Hard alloy material for optical mold and near-net forming preparation method of optical mold

    CN121449427A